Charles Bonnet Syndrome (CBS) in a Patient With Secondary Progressive Multiple Sclerosis: A Case Report - Shima Jahani; Atefeh Eidi Ardizi; MohammadAli Sahraian (Clinical Case Reports, 2025)
ABSTRACT Here we present a 69‐year‐old woman with Secondary Progressive Multiple Sclerosis (SPMS) and Charles Bonnet Syndrome. Our case underlines how clinicians should consider this rare syndrome in cognitively intact MS patients with visual hallucinations.